Penguatan Motivasi Belajar Peserta Didik pada Pembelajaran Pendidikan Agama Islam melalui Literasi Keagamaan Digital - Kurniawan, Rikza Syahrial; fahmi, Muhammad; Mas'ud, Ali; Syaifuddin, Syaifuddin (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2024)
The rapid development of today's digital world is both a challenge and an opportunity in the world of education, especially in Islamic Religious Education (PAI). New breakthroughs from educators are really needed in strengthening students' learning motivation so that they are always enthusiastic in the learning process. This research aims to examine the application of digital religious literacy as an effort to strengthen PAI and BP learning motivation in class XI students at SMA Negeri 1 Gedangan Sidoarjo. This research is a type of field research using a descriptive qualitative approach. The data collected is the result of observation, interviews and documentation through purposive sampling techniques. The technique used in data analysis goes through three stages, namely data condensation, data presentation and drawing conclusions. This research shows the results that the application of digital religious literacy has significantly strengthened the motivation to learn PAI and BP in class XI students at SMA Negeri 1 Gedangan Sidoarjo. This can be a guide for Islamic religious educators in designing relevant learning according to current developments and preparing students to face future challenges